2009
DOI: 10.1080/13102818.2009.10818560
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lactic Acid Bacteria from Dry Sausages

Abstract: Eight genera (Lactobacillus, Leuconostoc, Staphylococcus, Enterococcus, Lactococcus, Micrococcus, Streptococcus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We reported XOS utilization by Lactobacillus strains isolated from Bulgarian home artesian meat products [ 41 ]. About 30 strains identified as Lb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported XOS utilization by Lactobacillus strains isolated from Bulgarian home artesian meat products [ 41 ]. About 30 strains identified as Lb.…”
Section: Discussionmentioning
confidence: 99%
“…sakei was isolated from specific Bulgarian sausages. Previous analysis [ 41 ] showed that this strain possesses antimicrobial activity. Semi-quantitative analysis of the expression of genes involved in XOS metabolism indicated for the first time that Lb.…”
Section: Discussionmentioning
confidence: 99%
“…In this case all the three major clusters were divided into several subclusters, making this method more convenient for differentiation of closely related strains. If compared together, the results of the all four methods showed comparable results, the strains in the three major clusters probably reflecting the three predominant Lactobacillus species participating in the "Lukanka" ripening -L. plantarum, L. paraplantarum and L. pentosus (6). …”
Section: Resultsmentioning
confidence: 73%
“…One of the most important roles of Lactobacillus strains in this process is their acidifying properties for the conservation of the final product, depending as well of the total cell number, as of the acidifying properties of the particular strains. The aim of the study is the measurement of the acidifying properties of twenty-two Lactobacillus strains, isolated from "Lukanka" sausage and previously described (2).…”
Section: Introductionmentioning
confidence: 99%